Glycerol improves the productivity of the lipase inhibitory activity of streptomyces coelicolor - SUKRUTHA SURESH; VENKATA KRISHNA BAYINENI; RAVI KUMAR KADEPPAGARI (International Journal of Pharma and Bio Sciences, 2017)
Lipase inhibitory activity was confirmed in the submerged cultures of Streptomyces coelicolor during time course studies and addition of glycerol increased the production of this activity. Lipase inhibitory activity was increased with the increasing concentration of glycerol up to 2 %. There was a dramatic increase of the inhibitory activity on the 7th day of the submerged batch fermentation. However, there was no significant increase in the biomass suggesting the secondary metabolite characteristic of the inhibitory activity. The presence of glycerol in the submerged cultures increased the inhibitory activity by 3.4 times compared to the control on the 7th day. During fed-batch fermentation, feeding of glycerol to the submerged culture led to the increase of inhibitory activity by 9.7 times. These results suggest that glycerol can activate the pathways responsible for the production of the inhibitory activity. Improving the productivity of this lipase inhibitor will benefit the biotech and pharma sectors since this inhibitor can be a candidate for treating obesity due to its ability to inhibit lipase.